2009
DOI: 10.1158/1055-9965.epi-09-0782
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Dietary Patterns and Gastric Cancer Risk in Italy

Abstract: Background: There have been several studies on diet and gastric cancer, but only a few investigations have considered the role of dietary patterns. Methods: We investigated gastric cancer risk in relation to dietary patterns in a case-control study conducted in northern Italy between 1997 and 2007, including 230 patients with incident, histologically confirmed gastric cancer and 547 frequency-matched controls, admitted to the same hospitals as cases, with acute nonneoplastic conditions. Dietary habits were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…Towards this direction, the PCA provided three nutrient factors: the ''plant oil factor'', the ''vegetable/fruit factor'', and the ''animal food factor''. It must be noted that similar trends were observed in previous studies aiming at identifying dietary patterns based on nutrients ( (Bertuccio et al, 2009;Bravi et al, 2010), ''unsaturated fats'' (Bosetti et al, 2013;Edefonti et al, 2008), or ''vitamin E and PUFA'' (Berti et al, 2014). Consistent with our ''vegetable/fruit factor'', the ''vitamins and fiber'' (Bertuccio et al, 2009;Bosetti et al, 2013;Bravi et al, 2010;Edefonti et al, 2008) and ''antioxidants and fiber'' (Berti et al, 2014) factors are reported in the literature.…”
Section: Nutrient Factors and Their Functional Role On Cvd Risksupporting
confidence: 89%
“…Towards this direction, the PCA provided three nutrient factors: the ''plant oil factor'', the ''vegetable/fruit factor'', and the ''animal food factor''. It must be noted that similar trends were observed in previous studies aiming at identifying dietary patterns based on nutrients ( (Bertuccio et al, 2009;Bravi et al, 2010), ''unsaturated fats'' (Bosetti et al, 2013;Edefonti et al, 2008), or ''vitamin E and PUFA'' (Berti et al, 2014). Consistent with our ''vegetable/fruit factor'', the ''vitamins and fiber'' (Bertuccio et al, 2009;Bosetti et al, 2013;Bravi et al, 2010;Edefonti et al, 2008) and ''antioxidants and fiber'' (Berti et al, 2014) factors are reported in the literature.…”
Section: Nutrient Factors and Their Functional Role On Cvd Risksupporting
confidence: 89%
“…one study reported positive association between gastric cancer risk and "the animal products" dietary patterns (Bertuccio et al, 2009). another study reported that the risk of gastric cancer was higher with dietary pattern II (low consumption of fruit, salads, vegetables, dairy products, fish and meat) compared with dietary pattern I (high consumption of fruits and dairy products, and low consumption of alcoholic beverages (Bastos et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fruits and vegetables are important in diet as they contain a good range of nutrients, including vitamins, minerals, antioxidants and fibre and give the body the tools to heal itself. Dietary pattern rich in fruits and vegetables have a protective effect against gastric and colorectal cancer whereas a positive association was seen in between cancer and dietary patterns rich in meats, animal fats and starchy foods [10] . After diagnosis the subjects consumed plenty of fruits due to the beneficial effects of fruits against cancer.…”
Section: 11mentioning
confidence: 97%